Aramco World - Doughty Richard (Aramco Americas, 2021)
Woman on the Steppe and Pride of the Nation, Rust and Dreams on the Beirut - Damascus Railroad, The Sweetness of My Middle Eastern Vegan Kitchen, Egyptology's Eloquent Eye, Cumin.